MRI in cardio‐oncology: A review of cardiac complications in oncologic care. Issue 5 (26th August 2019) - Jeong, Daniel; Gladish, Gregory; Chitiboi, Teodora; Fradley, Michael G.; Gage, Kenneth L.; Schiebler, Mark L.
Abstract : From detailed characterization of cardiac abnormalities to the assessment of cancer treatment‐related cardiac dysfunction, cardiac MRI is playing a growing role in the evaluation of cardiac pathology in oncology patients. Current guidelines are now incorporating the use of MRI for the comprehensive multidisciplinary approach to cancer management, and innovative applications of MRI in research are expanding its potential to provide a powerful noninvasive tool in the arsenal against cancer. This review focuses on the application of cardiac MRI to diagnose and manage cardiovascular complications related to cancer and its treatment. Following an introduction to current cardiac MRI methods and principles, this review is divided into two sections: functional cardiovascular analysis and anatomical or tissue characterization related to cancer and cancer therapeutics. Level of Evidence: 5 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2019;50:1349–1366.